2021
DOI: 10.4314/bcse.v35i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Mn(II), Co(II), Ni(II), and Cu(II) complexes of amino acid derived Schiff base ligand: Synthesis, characterization and in-vitro antibacterial investigations

Abstract: Four complexes of Mn(II), Co(II), Ni(II) and Cu(II) with Schiff base ligand (H3L) derived from 2-amino-3-methylbutanoic acid and acetylacetonate were synthesized. All complexes were characterized by elemental analysis, Fourier-transform infrared spectroscopy and electronic spectroscopy. The results confirmed the coordination of the ligand to metals in tridentate fashion via the hydroxyl oxygen, the azomethine nitrogen and the enolic acetylacetonate oxygen. Antimicrobial activities were established for all comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Schiff bases based on isatin are highly soughtafter as antibacterial substances. The majority of infections that are acquired in hospitals and the general public are caused by Gram-positive and Gram-negative microorganisms [11][12][13][14][15]. The effectiveness of the drugs is declining daily as a result of the incorrect, prolonged, and widespread use of antibiotics, which has serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Schiff bases based on isatin are highly soughtafter as antibacterial substances. The majority of infections that are acquired in hospitals and the general public are caused by Gram-positive and Gram-negative microorganisms [11][12][13][14][15]. The effectiveness of the drugs is declining daily as a result of the incorrect, prolonged, and widespread use of antibiotics, which has serious health consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Salihović et al (2021) recently published a paper describing the synthesis, characterization and antimicrobial activity of some Schiff bases derived from Lcysteine and aldehydes. Literature data showed that most Co(II) complex compounds have better antimicrobial activity than the Schiff bases that were used as ligands (Nejo et al, 2010;Rajee et al, 2021;Siraj and Sanusi, 2021). Due to those above, we used the previously prepared Schiff base to synthesize new Co(II) complexes.…”
Section: Introductionmentioning
confidence: 99%